Self-reported home exercise adherence – fact or fiction? A validity and reliability study using concealed accelerometry among people with knee osteoarthritis - Nicolson, P; Hinman, R; Wrigley, T; Stratford, P; Bennell, K (Elsevier, 2018)
Purpose: To determine if sleep interventions improve pain and sleep in people with osteoarthritis and/or spinal pain. Methods: An electronic database search was conducted in Medline,Embase, AMED, PsycINFO, CENTRAL, CINAHL and PEDro from theirinception date to April 2016. Keywords relating to “sleep”, “osteoarthritis”, “spinal pain”, and “randomized control trial” were combined. Eligible studies were randomized control trials (RCT) from peer reviewed journals which investigated the use of sleep interventions for people with osteoarthritis and/or spinal pain. Sleep interventions were defined as interventions which aim to directly improve sleep related outcomes, including both non-pharmacological and pharmacological methods. Two investigators independently screened the literature search (title and abstract, followed by full text), extracted data and assessed methodological quality of included studies. Meta-analyses were performed to pool effect sizes for pain and sleep quality. Sensitivity analyses were performed with the following criteria: osteoarthritis or spinal pain, any sleep intervention, compared to a control/placebo group, 10 participants per group and PEDro Score6/10. The review protocol was registered with the International Prospective Register of Systematic Reviews (CRD42016036315). Results: Of 1199 unique records, 97 underwent full text screening and 22 studies were included. 14 studies examined spinal pain, six for osteoarthritis, and two were mixed. Sleep interventions were cognitive behavioural therapy (CBT) (n ¼ 8), pillows (n ¼ 4), sleep medication (n ¼ 3), exercise (n ¼ 2), massage (n ¼ 2), music (n ¼ 1), acupuncture (n ¼ 1), and mattresses (n ¼ 1). Intervention periods ranged from four to ten weeks. Seven studies combined sleep and pain interventions, however none combined CBT for sleep with exercise or physiotherapy. Overall pooled post-treatment results (mean age ¼ 33-73 years, n ¼ 1339) had high heterogeneity scores ranging from 62-95%. Random effects estimates showed that sleep interventions led to significant improvements in pain (standardized mean difference 4.94, 95% confidence interval [1.47-8.42], P ¼ 0.005) and sleep quality (9.13, [4.36-13.90], P<0.001). After sensitivity analyses, 7 RCTs were incorporated into the meta-analysis (mean age ¼ 42 to 72 years, n ¼ 354), with heterogeneity scores ranging from 10-45%. The pooled fixed effect estimates showed significant improvements in pain (10.78, [6.84- 14.72]; P<0.001) and sleep quality (8.21, [4.83-11.58]; P<0.001). Conclusions: Sleep interventions alone are likely to improve pain and sleep quality for people with osteoarthritis and/or spinal pain. Although the magnitude of change may not be clinically significant, further highquality studies using CBT for sleep in conjunction with other interventions for people with osteoarthritis and/or spinal pain should be conducted